2019
DOI: 10.1038/s42003-018-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Z-DNA and Z-RNA in human disease

Abstract: Left-handed Z-DNA/Z-RNA is bound with high affinity by the Zα domain protein family that includes ADAR (a double-stranded RNA editing enzyme), ZBP1 and viral orthologs regulating innate immunity. Loss-of-function mutations in ADAR p150 allow persistent activation of the interferon system by Alu dsRNAs and are causal for Aicardi-Goutières Syndrome. Heterodimers of ADAR and DICER1 regulate the switch from RNA- to protein-centric immunity. Loss of DICER1 function produces age-related macular degeneration, a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(151 citation statements)
references
References 100 publications
2
148
1
Order By: Relevance
“…In keratinocytes, RIPK1 ablation or disruptive mutation of the RHIM of RIPK1 induces spontaneous ZBP1dependent necroptosis and triggers skin inflammation, indicating that RIPK1 acts as a molecular scaffold to inhibit ZBP1-RIPK3-MLKL signaling in a RHIM-dependent way (Dannappel et al, 2014;Lin et al, 2016;. ZBP1 contains two tandem N-terminal Z-form nucleic acid binding (Zα)-domains, which specifically interact with doublestranded (ds) nucleic acid helices in the Z-conformation, including Z-RNA and Z-DNA (Herbert, 2019). Others and our group have shown that engagement of ZBP1 upon virus infection crucially depended on nucleic acid sensing by intact Zα-domains (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In keratinocytes, RIPK1 ablation or disruptive mutation of the RHIM of RIPK1 induces spontaneous ZBP1dependent necroptosis and triggers skin inflammation, indicating that RIPK1 acts as a molecular scaffold to inhibit ZBP1-RIPK3-MLKL signaling in a RHIM-dependent way (Dannappel et al, 2014;Lin et al, 2016;. ZBP1 contains two tandem N-terminal Z-form nucleic acid binding (Zα)-domains, which specifically interact with doublestranded (ds) nucleic acid helices in the Z-conformation, including Z-RNA and Z-DNA (Herbert, 2019). Others and our group have shown that engagement of ZBP1 upon virus infection crucially depended on nucleic acid sensing by intact Zα-domains (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The idea that ADAR1 could interact with DNA structure dates back to original observations made by Rich and colleagues who suggested that the Z-alpha domain of ADAR1 recognizes an alternative left-handed DNA structure 12,13,34 . Over the years, a very strong case has been made for the existence of Z-DNA and its role in many biological processes, particularly transcriptional regulation [37][38][39][40] . Specifically, it has been reported that Z-DNA is related to both transcriptional activation 41,42 and inhibition 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether RNA or DNA serve as agonists for ZBP1 in RIPK1-deficient keratinocytes remains to be determined. Zα-domains found in ZBP1 and the RNA editing enzyme ADAR1 specifically bind to nucleic acids in the Z-conformation, including Z-RNA and Z-DNA (Herbert, 2019). How dsRNA or dsDNA are stabilised in the thermodynamically unfavourable Z-conformation in living cells is unknown.…”
Section: Zbp1 Activation By Endogenous Nucleic Acids Induces Necroptomentioning
confidence: 99%
“…In keratinocytes, ablation of RIPK1 or disruptive mutation of the RHIM of RIPK1 induces spontaneous ZBP1-dependent necroptosis and triggers skin inflammation, indicating that RIPK1 acts as a molecular scaffold to inhibit ZBP1-RIPK3-MLKL signalling in a RHIM-dependent way (Dannappel et al, 2014;Lin et al, 2016;. ZBP1 contains two tandem N-terminal Z-form nucleic acid binding (Zα)-domains, which specifically interact with double stranded (ds) nucleic acid helices in the Z-conformation, including Z-RNA and Z-DNA (Herbert, 2019). Others and our group have shown that engagement of ZBP1 upon virus infection crucially depended on nucleic acid sensing by intact Zα-domains (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%